Comparison of lipid and lipoprotein values among male elite student-athletes and students receiving sports training - Aksu, Aykut; İmamoğlu, Osman; Karacabey, Kürşat (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
This study aimed to compare the lipid and lipoprotein values of elite male athletes and male students receiving sports training, and to investigate the risks of cardiovascular disease. A total of 209 male students who received sports training at the Ondokuz Mayıs University were included. Fasting blood samples were taken from the subjects' antecubital vein 48 hours before the exercise sessions. Triglyceride (TG), total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C) levels were determined using the Hitachi 717 Auto Analyzer. The students were similar in age, training age, height, body weight and body mass index (BMI). No significant difference was found in TG levels (p>0.05)), but TC, HDL-C, LDL-C, apolipoprotein A1 (Apo A1), apolipoprotein B (Apo B), and lipoprotein(a) [(Lp(a)] differed significantly (p<0.05 and p<0.001). Moreover, a statistical difference was found in serum lipid value according to the ratios of TC/HDL-C, LDL-C/HDL-C and Apo-B/Apo-A1 (p<0.001). Differences were found in lipid and lipoprotein values of elite athletes and students receiving sports training. Although all values were within normal limits, elite wrestlers had worse levels than other athletes and students. No group was at risk for cardiovascular diseases.